Solos expansivos no contexto do território brasileiro: Revisão sistemática com análise bibliométrica da literatura (Research, Society and Development, 2025)
Expansive soils are unsaturated materials that can decrease or increase in volume when their moisture content changes. Understanding soil expansivity is essential for the planning and execution of engineering projects, preventing disruptions and emergency actions caused by expansion-related pathologies. Thus, this article aimed to present a systematic review with a bibliometric analysis, seeking to understand expansive soils in the context of the Brazilian territory. The study was developed in four stages: database article search, meta-analysis, bibliometric analysis, and systematic analysis. The data search was carried out in the Scopus database using the PRISMA method for article selection. In the meta-analysis, bibliometric and specific publication data were extracted, and the bibliometric analysis was conducted both quantitatively and qualitatively using VOSviewer and Microsoft Excel software. In the systematic analysis, the information was synthesized. Fourteen articles published between 2013 and 2022 were included. Most authors and institutions are from the Northeast and South regions, highlighting the need to expand studies to other areas. The co-authorship networks revealed limited collaboration between authors and international institutions. The topic has mainly been approached through studies focused on the physical, chemical, mineralogical, hydrological, and mechanical characterization of expansive soils, as well as on improvement techniques. It is concluded that it is relevant to develop research on the hydromechanical behavior at micro and macro scales and on solutions that reduce the expansivity potential, minimizing risks in engineering projects.